ANALISIS PENGELOLAAN PERSEDIAAN BAHAN BAKU UNTUK MEMENUHI KEBUTUHAN PRODUKSI PADA TAICHAN CUANGKY - Rosalia, Rosalia; Noorhya Akhmar Ramadhan Putri, Eva; Hendra, Hendra (Jurnal GeoEkonomi, 2025)
This study aims to analyze the management of standard material inventory at the SME Taichan Cuangky by implementing the Just In Time (JIT) method to improve operational efficiency and reduce waste. As one of the SMEs in the culinary sector, Taichan Cuangky faces challenges in inventory management, such as high storage costs, frequent ordering, and the risk of losses due to supply instability. Therefore, this research evaluates the effectiveness of JIT in meeting production needs efficiently while comparing it with the conventional system and the Economic Order Quantity (EOQ) method. This study employs a narrative approach with quantitative analysis. Data were collected through observations, interviews, and document analysis from July 2023 to June 2024. The results show that the implementation of JIT provides significant efficiency improvements. Annual inventory costs drastically decreased from IDR 18,187,425 (conventional system) to IDR 1,499,699.97, and the ordering frequency was reduced from 48 times to once per year. The JIT method also improved storage space efficiency and reduced the risk of overstocking. Although JIT delivers significant cost savings, its success highly depends on the reliability of suppliers in delivering raw materials on time. This study suggests integrating JIT with a more accurate demand forecasting system to mitigate the risks of supply chain disruptions and ensure production continuity. In conclusion, JIT proves effective in enhancing operational efficiency in SMEs within the culinary sector. Further research could explore the adaptation of JIT for larger-scale enterprises and other sectors.